Taxonomic diversity of microbial communities in the cold sulfur spring Bezymyanny (Pribaikalsky district, Republic of Buryatia) - T. G. Banzaraktsaeva; E. V. Lavrentyeva; V. B. Dambaev; I. D. Ulzetueva; V. V. Khakhinov (Вавиловский журнал генетики и селекции)
The environmental conditions of cold sulfur springs favor the growth and development of abundant and diverse microbial communities with many unique sulfur cycle bacteria. In this work, the taxonomic diversity of microbial communities of three different biotopes (microbial mat, bottom sediment, and water) in the cold sulfur spring Bezymyanny located on the shore of Lake Baikal (Pribaikalsky district, Republic of Buryatia) was studied using highthroughput sequencing of the 16S rRNA gene. By sequencing the microbial mat, bottom sediment, and water samples, 76,972 sequences assigned to 1,714 ASVs (ASV, amplicon sequence variant) were obtained. Analysis of the ASV distribution by biotopes revealed a high percentage (66–93 %) of uniqueness in the three communities studied. An estimate of the alpha diversity index showed that bottom sediment community had higher indices, while microbial mat community was characterized by a lowest diversity. Bacteria of the phyla Pseudomonadota, Bacteroidota, Campylobacterota, Actinomycetota, Desulfobacterota dominated in different proportions in the studied communities. The features of the community structure of the studied biotopes were established. The microbial mat community was represented mainly by Thiothrix (43.2 %). The bottom sediment community was based on Sulfurovum (11.2 %) and co-dominated by unclassified taxa (3.2–1 %). Sequences assigned to the genera Novosphingobium, Nocardioides, Legionella, Brevundimonas, Sphingomonas, Bacillus, Mycobacterium, Sphingopyxis, Bradyrhizobium and Thiomicrorhabdus were found only in the water microbial community. Sulfur-oxidizing bacteria (SOB) and sulfate-reducing bacteria (SRB) were identified in all the communities studied, which indicates the ongoing processes of the sulfur cycle in the Bezymyanny spring ecosystem. It should be noted that sequences of unclassified and uncultivated sulfur cycle bacteria were present in all communities and a significant proportion of sequences (20.3–53.9 %) were not classified.